Pengaruh Perbedaan Warna Wadah Kultur Terhadap Kandungan Karotenoid Ikan Badut (Amphiprion ocellaris) - DiazGonzales, Syifa Maria; Julyantoro, Pande Gde Sasmita; Pebriani, Dewa Ayu Angga (Current Trends in Aquatic Science; Vol 3 No 1 (2020), 2020)
Ornamental fish, both freshwater and seawater fish, are commodities that are in great demand by the community and have a great opportunity to be developed. Pigmentation in ornamental fish has an important role in the brightness of fish colour. Clown fish (Amphiprion ocellaris)  is one of the ornamental fishes that requires carotenoids as a source of nutrition in the formation of  body colour. The purpose of this research is to investigated the effect of different colour of culture containers on the quality improvement of the clown fish body colour and on the of growth and survival rate of cultured clown fish. The research method used was an experimental method. The size of clown fish used in this study were 4-5 cm and cultured in black, white, blue, and yellow containers. The results of this study showed that the colour of different maintenance containers has no effect on the total value of carotenoids found in skin or fish fins. However, visually the colour of different maintenance containers has an influence on each colour of the clown fish. The best value for total carotenoids was obtained using a white colour container. The growth rate at each treatment shows a difference in each week. Clown fish have the ability to live in bright and dark environmental conditions, therefore the treatment of different container colours does not affect the survival of clown fish.